1992
DOI: 10.1597/1545-1569_1992_029_0174_rairtp_2.3.co_2
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Activities in Relation to Palatal Muscle Contraction

Abstract: This study Investigated the activities of the tensor and levator veli palatini muscles related to respiration. During quiet breathing, no activity was observed in either muscle. With either hypercapnic or hypoxemic condition, the tensor veli palatini muscle exhibited phasic activity during inspiration. The levator veli palatini muscle showed phasic activity during expiration with hypoxemia (PaO2 < 40 mm Hg). NaCN perfused bilaterally through the carotid sinus induced these respiratory activities. The tensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…This result is presumed to reflect an increase in the strength of the bilateral BM and the OOM. Our findings are congruent with those of a previous study by Yanagisawa et al 21 that showed that EMST was a good expiratory training method that included various oral muscles, including the levator veli palatini and the BM 22 . In particular, EMST requires high intraoral pressure as an expiratory activity against resistance, which is achieved through the contraction of both the cheeks.…”
Section: Discussionsupporting
confidence: 93%
“…This result is presumed to reflect an increase in the strength of the bilateral BM and the OOM. Our findings are congruent with those of a previous study by Yanagisawa et al 21 that showed that EMST was a good expiratory training method that included various oral muscles, including the levator veli palatini and the BM 22 . In particular, EMST requires high intraoral pressure as an expiratory activity against resistance, which is achieved through the contraction of both the cheeks.…”
Section: Discussionsupporting
confidence: 93%
“…EMST is known to aid in strengthening of various oral and pharyngeal muscles, such as the oropharyngeal, laryngeal, supralaryngeal and levator veli palatini muscles, as well as the suprahyoid muscles, as involved in swallowing (40)(41)(42). In particular, the levator veli palatini muscle is known to play an essential role in the prevention of aspiration during swallowing (42). Moreover, afferent stimulation of the peripheral sensory receptors of the tongue and oropharynx increases the activity of the swallowing centre located in the brain stem (43).…”
Section: E F F E C T S O F E M S T O N S T R O K E W I T H D Y S P H mentioning
confidence: 99%
“…The levator veli palatini is a major muscle that elevates and retracts the velum to implement velopharyngeal closure. Levator veli palatini muscle activity is enhanced with expiratory phase like other expiratory muscles [119]. The adequate function of the levator veli palatini is important to reduce or prevent aspiration during swallowing.…”
Section: Expected Outcomes With Emstmentioning
confidence: 99%